FORMULATION AND EVALUATION OF IN SITU MUCOADHESIVE THERMOREVERSIBLE NASAL GEL OF SERTRALINE HYDROCHLORIDE - DIKSHA SHARMA,; SHAWETA AGARAWAL, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to aiming to formulate and evaluate temperature based in situ nasal gel of sertraline HCL. Materials and Methods: Preformulation studies of sertraline hydrochloride including tests for identification, solubility studies, Fourier-transformer infrared (FTIR) spectroscopy, melting point determination, and other studies were carried out and compared with the specification as per literature. The solubility of sertraline hydrochloride was determined in different solvents such as in distilled water, ethanol, acetone, isopropyl alcohol, and 2-propanol. Each value for solubility was determined in triplicate and average values were reported. The drug excipient compatibility study was determined by FTIR. Thermal analysis was performed using a differential scanning calorimetric equipped with a computerized data station. The UV spectrum of sertraline hydrochloride was obtained using UV JascV630. The in situ gel formulation was prepared by changing the concentration and using only one polymer (Carbopol 934) has been used at the same concentration. Mucoadhesive strength and in vitro permeation study were determined using gout nasal mucosal membrane, whereas in vitro drug release study was carried out using diffusion cell through egg membrane as a biological membrane. The stability studies were conducted according to ICH guidelines. Results: The FTIR studies of formulation show no interaction between drug and excipient. In situ gel was prepared using Carbopol 934 and Poloxamer 407 to improve its adhesion property. The optimized formulation (F6) was transparent and clear in appearance with 101.15% drug content. The sol-gel transformation of in situ gel was found at temperature 34.92°C with immediate gelation property. The in vitro drug release of optimized formulation was found 95.80% drug release in 8 h. Formulations F4 and F6 showed immediate gelation within 60 s and remained stable for an extended period. All the formulations were liquid at room temperature and underwent rapid gelation on contact with simulated nasal fluid. Conclusion: The results concluded that the formulations of in situ nasal gel showing to improve the bioavailability through its longer residence time and ability to sustain drug release.